Influence of Quality of Health Services on Patient Satisfaction in Islamic Hospital "X" in 2021 - Dwiki Hastomo Putra; Fauzan Firdaus; Muhammad Dzikri Mustofa; Muhammad Uweis Al-Qorny Virdinant (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
Hospital is a health service institution that provides complete individual health services that provide inpatient, outpatient, and emergency services. Indeed, a health service provider can provide maximum service by the expectations and desires of patients. This research is in the form of qualitative and uses a Cross-Sectional study to see the relationship between the quality of services provided to patient satisfaction at Islamic Hospital X in 2021. The data collection procedure was carried out by observation, interviews, and literature studies that took place from May to July 2021. The results showed that based on the dimensions of Reliability, Responsiveness, Assurances, It can be seen from the alertness indicators of health workers, the availability of adequate and modern medical devices, communication skills of health workers, the appearance of health workers, in general, showing good results and leading to patient satisfaction with the services received at Islamic Hospital X in 2021.